Occurrence of multiple drug resistant Escherichia coli and Enterococcus species in village chickens from four farms in Selangor, Malaysia - Ahmad, Nur Indah; Bejo, Siti Khairani; Nik Mohd Azmi, Nik Mohd Faiz; Japri, Muhammad Syazani (2019)
Intensification of poultry farming is associated with the use of antimicrobial agents either as growth promoters, feed additives or prophylaxis, leading to antimicrobial resistant bacteria in chickens which may serve as a risk to human health via the food chain. In Malaysia, village chickens has built its reputation among the locals as an alternative source of protein, perceived to be free from hazards associated with commercial poultry farms including drug residues and poor animal welfare. Nevertheless hazards including antimicrobial resistant bacteria may still occur in village chickens since birds are reared outdoors and fed with food- or agro-based wastes. Therefore, this study aimed to determine if antimicrobial resistance is prevalent in 2 commensal bacterial species in the poultry intestinal tract; Escherichia coli and Enterococcus spp. Cloacal swabs were acquired from 60 village chickens on 4 farms in the Hulu Langat district, Selangor, Malaysia. Escherichia coli and Enterococcus spp. were isolated from the samples with the overall prevalence of 89.3% and 37.5%, respectively. E. coli isolates were resistant to tetracycline (78%), ampicillin (56%), amoxicillin (52%), streptomycin (38%), chloramphenicol (34%), cephalexin (28%), enrofloxacin (24%), gentamicin (8%) and aztreonam (2%), but susceptible to meropenem. Enterococcus spp. isolates were resistant to tetracycline (100%), norfloxacin (72%), enrofloxacin (52%) gentamicin (33%), ciprofloxacin (33%), ampicillin (29%) and amoxicillin (10%), but susceptible to vancomycin. Overall, multiple drug resistance in the village chicken isolates were determined as high E. coli (59%) and Enterococcus spp. (67%), considering the nature of the farming system adopted.